2020
DOI: 10.3390/molecules25071750
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 18F-PM-PBB3 (18F-APN-1607) Uptake in the rTg4510 Mouse Model of Tauopathy

Abstract: Misfolding, aggregation, and cerebral accumulation of tau deposits are hallmark features of Alzheimer’s disease. Positron emission tomography study of tau can facilitate the development of anti-tau treatment. Here, we investigated a novel tau tracer 18F-PM-PBB3 (18F-APN-1607) in a mouse model of tauopathy. Dynamic PET scans were collected in groups of rTg4510 transgenic mice at 2–11 months of age. Associations between distribution volume ratios (DVR) and standardized uptake value ratios (SUVR) with cerebellum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…We also used APN-1607 (also known as PM-PBB3), a PET tracer known to fluorescently label various aggregates tau species but not monomeric tau. 54,55 We found significant fluorescence labeling in the CA1 region of 22month-old App NL-G-F rat brain, similar to that in 3× Tg-AD mice (positive control) (Fig. 2j).…”
Section: Generation Of the App Knock-in Ratssupporting
confidence: 65%
“…We also used APN-1607 (also known as PM-PBB3), a PET tracer known to fluorescently label various aggregates tau species but not monomeric tau. 54,55 We found significant fluorescence labeling in the CA1 region of 22month-old App NL-G-F rat brain, similar to that in 3× Tg-AD mice (positive control) (Fig. 2j).…”
Section: Generation Of the App Knock-in Ratssupporting
confidence: 65%
“…However, interpretation of PET results obtained with first-generation tau tracers can be made difficult by off-target tracer binding to neuromelanin and/or hemorrhagic lesions, as well as by the use of MAOI 23 , 38 . Although 18 F-THK5351 PET and MR images were carefully matched, our results should be interpreted cautiously and require confirmation in future independent studies using second-generation tau ligands—including MK-6240, 18 F-JNJ64349311, and 18 F-APN1607 39 , 40 .…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the second-generation [ 18 F]PM-PBB3 with improved binding properties was developed to overcome the limitations. Similar observations were reported by Tagai et al (2020) and Weng et al (2020) using [ 18 F]PM-PBB3 in rTg4510 mouse models with increased tracer retention in the cortical and hippocampal regions. Among the other second-generation tau tracers, [ 18 F]JNJ-64349311 ( Declercq et al, 2017 ) and [ 18 F]PI-6240 ( Kroth et al, 2019 ) have so far been reported in wild-type mice for brain uptake and biodistribution assessment.…”
Section: Tau Imagingsupporting
confidence: 89%